Overview of Risk-Estimation Tools for Primary Prevention of Cardiovascular Diseases in European Populations. - Gorenoi, Vitali; Hagen, Anja (Central European Journal of Public Health, 2015)
To identify persons with a high risk for cardiovascular diseases (CVD) special tools (scores, charts, graphics or computer programs) for CVD-risk assessment based on levels of the certain risk factors have been constructed. The applicability of these instruments depends on the derivation cohorts, considered risk factors and endpoints, applied statistical methods as well as used formats. The review addresses the risk-estimation tools for primary prevention of CVD potentially relevant for European populations. The risk-estimation tools were identified using two previously published systematic reviews as well as conducting a literature search in MEDLINE and a manual search. Only instruments were considered which were derived from cohorts of at least 1,000 participants of one gender without pre-existing CVD, enable risk assessment for a period of at least 5 years, were designed for an age-range of at least 25 years and published after the year 2000. A number of risk-estimation tools for CVD derived from single European, several European and from non-European cohorts were identified. From a clinical perspective, seem to be preferable instruments for risk of CVD contemporary developed for the population of interest, which use easily accessible measures and show a high discriminating ability. Instruments, restricting risk-estimation to certain cardiovascular events, recalibrated high-accuracy tools or tools derived from European populations with similar risk factors distribution and CVD-incidence are the second choice. In younger people, calculating the relative risk or cardiovascular age equivalence measures may be of more benefit.